ETS1 polymorphism rs73013527 in relation to serum RANKL levels among patients with RA. Issue 5 (5th February 2021) - Yang, Bin; Luo, Limei; Chen, Lin; Niu, Qian; Zhang, Junlong; Xu, Huan; Wu, Yifeng; Huang, Zhuochun
Abstract : Abstract: We previously identified E26 transformation specific sequence 1 (ETS1) rs73013527 single nucleotide polymorphism associated with RA susceptibility and disease activity. In the present study, we aims to further investigate the association between ETS1 rs73013527 and receptor activator of nuclear factor kappa B ligand (RANKL), an index related to bone destruction and was reported to elevate in RA. We determined genotypes of ETS1 rs73013527, serum RANKL concentration, clinical characteristics (disease duration, disease activity score for 28 painful/swollen joints), and laboratory markers (rheumatoid factor, anti-citrullinated protein antibody, anti-keratin antibody, c-reactive protein, erythrocyte sedimentation rate) of 254 RA cases. Univariate and multivariate analysis were employed to explore the association between ETS1 rs73013527 and serum RANKL levels in RA patients. Univariate and multivariate analysis indicated no association of serum RANKL levels with patient age, gender, clinical characteristics, and laboratory markers. Univariate analysis, not multivariate analysis indicated genotype CT/TT of ETS1 rs73013527 was significantly associated with elevated RANKL levels in RA patients. ETS1 rs73013527 is in relation to serum RANKL levels among patients with RA. ETS1 probably might be an indirect factors involved in RANKL regulation in RA.